Mastery concepts and misconceptions in biotechnology courses with a three tier diagnostic test - Idris, Tengku; Hidayat, Topik; Rahmat, Adi (Universitas Negeri Jakarta, 2024)
This research aims to determine the mastery of concepts and misconceptions of students in the Biology Education Study Program wich is in Pekanbaru. This type of research is survey research with a porpusive sampling type. The population of the study was all students who had taken biotechnology courses, while the research sample was 6th semester students who had just completed biotechnology courses in the previous semester. The total research sample was 32 students. The instrument used to measure mastery of concepts and misconceptions is a diagnostic test with 20 multiple choice questions accompanied by reasons and level of belief. The questions are given using a Google form and students work on the questions during class and are given 90 minutes.The research data were analyzed descriptively. Based on the results showed that for indicator 1 30.01% of students understood the basic concepts of biotechnology well and 55.63 had misconceptions. In indicator 2, only 5% of students understood the concept of biotechnology process while 64.38% had misconceptions and 29.38 did not understand the concept. Indicator 3, as many as 10.63% of students understand the concept of conventional and modern biotechnology characteristics and 59.38% of students have misconceptions and 25.63% do not understand the concept while indicator 4 as many as 30.63% of students understand the examples of biotechnology products while still 43.13% have misconceptions and 22.50% still do not understand the concept. Students' mastery of concepts in biotechnology courses is in a very low category and while more than half of the students still experience misconceptions and do not understand the concepts.